Integrated Optimization Algorithm in Solving Economic Dispatch Problems - Ismail N.L.; Musirin I.; Dahlan N.Y.; Mansor M.H.; Sentilkumar A.V. (Institute of Electrical and Electronics Engineers Inc., 2024)
The utilization of conservative fossil fuels in power generation has played a significant role in driving economic growth, but it has also resulted in adverse consequences towards environmental impacts. This study proposed Multi-objective Hybrid Evolutionary Programming-Barnacles Mating Optimization as a solution to address the Combined Economic Environmental Dispatch problem by weighted-sum method implementation. The bi-objective function are the minimizing of the total generation cost and total emission have been optimized simultaneously. The performance of the algorithm is evaluated on Reliability Test System IEEE 57-Bus consisting of 7 generating units that consider ramp rate limits generator constraint. The proposed algorithm has been compared with the existing techniques, Multi-objective Barnacles Mating Optimizer and Multi-objective Evolutionary Programming. The results reveal that MOHEBMO generates superior and consistent solutions. 2023 IEEE.